High‐Throughput Image Cytometry Detection Method for CAR‐T Transduction, Cell Proliferation, and Cytotoxicity Assays. Issue 7 (28th November 2020) - Wang, Yufei; Chan, Leo Li‐Ying; Grimaud, Marion; Fayed, Atef; Zhu, Quan; Marasco, Wayne A.
Abstract: Chimeric antigen receptor (CAR)‐T cell therapy has drawn much attention due to its recent clinical success in B‐cell malignancies. In general, the CAR‐T cell discovery process consists of CAR identification, T‐cell activation, transduction, and expansion, as well as assessment of CAR‐T cytotoxicity. The current evaluation methods for the CAR‐T discovery process can be time‐consuming, low‐throughput and requires the preparation of multiple sacrificial samples in order to produce kinetic data. In this study, we employed the use of a plate‐based image cytometer to monitor anti‐CAIX (carbonic anhydrase IX) G36 CAR‐T generation and assess its cytotoxic potency of direct and selective killing against CAIX + SKRC‐59 human renal cell carcinoma cells. The transduction efficiency and cytotoxicity results were analyzed using image cytometry and compared directly to flow cytometry and Chromium 51 ( 51 Cr) release assays, showing that image cytometry was comparable against these conventional methods. Image cytometry method streamlines the assays required during the CAR‐T cell discovery process by analyzing a plate of T cells from CAR‐T generation to in vitro functional assays with minimum disruption. The proposed method can reduce assay time and uses less cell samples by imaging and analyze the same plate over time without the need to sacrifice any cells. The ability to monitor kinetic data can allow additional insights into the behavior and interaction between CAR‐T and target tumor cells. © 2020 International Society for Advancement of Cytometry